Biomechanical Indicators of the Corner Kick Skill for the Far Area and Their Relationship with the Accuracy of Performance among Premier League Football Players - Abdel Reda, Karar Abdel Amir; Jabbar, Haydar Shamkhi (Journal of Neonatal Surgery, 2025)
The importance of the research in studying the biomechanical indicators of the skill of executing the corner kick for the player executing the far area and the extent of its relationship to the accuracy of performance to understand the method of performance and reveal the interconnected relationships between the movement of body parts during performance, as well as determining the motor procedures required to accomplish this performance with the highest possible efficiency and with the least possible effort to achieve the accuracy of execution and deliver the ball to the attacking player to achieve goals. The research problem results from the researcher’s observation, follow-up, and experience as a former player of the developments in this game the lack of studies that addressed this skill in the mechanical field, and the lack of values ​​for its biomechanical variables. The researcher decided to study this skill mechanically in addition to discovering the appropriate and correct movement infiltration of the executing player as well as discovering the weak points and avoiding them and strengthening the positive side to reach the player to the optimal performance to achieve the required accuracy and ideal performance. The objectives of the research were to identify some biomechanical indicators of the skill of executing the corner kick in football for advanced players and its relationship to accuracy and to identify the nature of the relationship between some biomechanical indicators of the skill of executing the corner kick In football for advanced accuracy, the researcher used the descriptive approach using the correlation study method, which is the optimal method to solve the research problem. The research community was deliberately determined, represented by the Premier League football teams for the 2024-2025 football season, namely Al-Nasiriyah Club - Al-Gharraf Club from Dhi Qar Governorate, Southern Refineries Club and Al-Bahri Club from Basra Governorate. Three players were selected from each team, making the sample (12) players proficient in performing the corner kick with the right foot. The selection of players was based on personal interviews conducted by the researcher with the coaches of those teams to name the players who implemented this method. One of the most important conclusions is that there is a significant correlation between the biomechanical variables and the accuracy of the far-area corner kick skill.